2020
DOI: 10.21037/tcr-19-2870
|View full text |Cite
|
Sign up to set email alerts
|

Differences among the Thyroid Imaging Reporting and Data System proposed by Korean, the American College of Radiology and the European Thyroid Association in the diagnostic performance of thyroid nodules

Abstract: The aim of this study was to evaluate the diagnostic performance of the Thyroid Imaging Reporting and Data System (TIRADS) in the forms proposed by Kwak (K-TIRADS), the American College of Radiology (ACR-TIRADS) and the European Thyroid Association (EU-TIRADS). A total of 846 thyroid nodules were evaluated by K-TIRADS, ACR-TIRADS and EU-TIRADS. All the ultrasound data were analyzed and classified according to the criteria of the three systems. In addition, we calculated the risk of malignancy and plotted recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
4
11
0
Order By: Relevance
“…Thyroid cancer is the most common malignant tumor of the endocrine system and the head and neck system. DTC accounts for more than 90% of all thyroid cancer pathologies ( 1 ). The prognosis of patients with DTC is generally good with conventional treatment (surgical resection and postoperative therapy with 131 I and endocrine suppression therapy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroid cancer is the most common malignant tumor of the endocrine system and the head and neck system. DTC accounts for more than 90% of all thyroid cancer pathologies ( 1 ). The prognosis of patients with DTC is generally good with conventional treatment (surgical resection and postoperative therapy with 131 I and endocrine suppression therapy).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients are effectively treated with radioactive iodine, however, clinical observations have revealed that some patients with lesions Original Article Effect of monocarboxylate transporter-1 on the biological behavior of iodine-refractory thyroid carcinoma are insensitive to or unable to intake radioactive iodine, which results in the lesions becoming more malignant and a poor therapeutic effect. Radioiodine-refractory DTC (RAI-R DTC) (1) refers to a type of DTC that has lost the ability to intake iodine. Monocarboxylate transporter-1 (MCT 1 ) is a member of the monocarboxylate transporter (MCT) family of proteins that are mainly involved in lactate transport across membranes (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater the hardness of the nodule, the more malignant it will be. Although CEUS and UE have high value in the qualitative diagnosis of nodules, the accuracy of using only one of them for the clinical diagnosis of TI-RADS 4 types of nodules is still not ideal (8,9). To achieve the purpose of improving diagnosis, the diagnosis of TI-RADS 4 nodules was based on direct observations of the lesion signals in the previous study about the combined diagnosis of TI-RADS 4 nodules by CEUS and UE (10)(11)(12), which obviously produced diagnostic bias.…”
Section: Introductionmentioning
confidence: 99%
“…There are various methods of the thyroid gland visualization nowadays including TIRADS (Thyroid Image Reporting and Data System); first proposed in 2009 by Horvath E. et al, subsequently modified by Kwak et al in 2011 (K-TIRADS), the American College of Radiology (ACR-TIRADS) and the European Thyroid Association (EU-TIRADS) [4,5,6]. According to Shi et al, the sensitivity of K-TIRADS is higher than that of ACR-TIRADS and EU-TIRADS, while ACR-TIRADS and EU-TIRADS have a higher specificity [6]. The creation of these thyroid imaging systems is intended to help with the diagnosis of nodal formations estimating the risk of malignancy in each category [7].…”
Section: Introductionmentioning
confidence: 99%